Effects of Rosemary Extracts on Textural and Functional Qualities of Surimi Gel from Striped Catfish (Pangasianodon hypophthalmus) (Sauvage, 1878) during refrigerated storage - Maurya, Pradip K.; Majumdar, Ranendra K.; Saha, Apurba; Dhar, Bahni; Singh, Asem Sanjit (Fishery Technology, 2018)
Effects of aqueous and ethanolic extracts of rosemaryleaf on textural and functional properties ofsurimi gel from striped catfish (Pangasianodonhypophthalmus) (Sauvage, 1878) during refrigeratedstorage was evaluated. The properties of surimi gelsuch as gelling, water holding capacity, proteinsolubility, texture profile, whiteness, as well as thequality indices like total volatile bases andthiobarbituric acid values were estimated periodicallyduring a refrigerated storage period of 20 days.Increase of water holding capacity in rosemaryextract added gels indicated stronger protein networkformation, whereas, protein solubility decreasedsignificantly in all the groups as the storageprogressed indicating the formation of proteinaggregates. Thiobarbituric acid value, indicative oflipid oxidation decreased in treated samples but atdifferent rates, depending upon the concentration ofrosemary extract. Gel strength of samples wasaffected upon incorporation of rosemary extract andtreated groups showed higher values than thecontrol, indicating the positive role of rosemary’sphenolics in cross linking of protein-protein interaction.Textural attributes were found to be affectedmost due to addition of rosemary. The controlsamples tended to have the largest decreasing rateof whiteness during the period of storage, comparedto the treated groups (0.25-0.75%). Both the extractsof rosemary at higher concentration (0.75%) showedhighest consumer acceptability on day-1 and also atthe end of the storage period. On the basis of sensory evaluation the control was acceptable only upto 12 days.